Answer:
A
Explanation:
Given the 2 equations
y = x² + 8x + 2 → (1)
y = 7x + 4 → (2)
Substitute y = x² + 8x + 2 into (2)
x² + 8x + 2 = 7x + 4 ( subtract 7x + 4 from both sides )
x² + x - 2 = 0 ← in standard form
(x + 2)(x - 1) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 2 = 0 ⇒ x = - 2
x - 1 = 0 ⇒ x = 1
Substitute these values into (2) for the corresponding values of y
x = - 2 : y = - 14 + 4 = - 10 ⇒ (- 2, - 10)
x = 1 : y = 7 + 4 = 11 ⇒ (1, 11)
The solutions are (- 2, - 10) and (1, 11) → A